The Role of Economic and Social Safety Nets in Extreme Poverty in Indonesia - Setyadi, Sugeng; Indriyani, Lili; Widiastuti, Anita (ETIKONOMI, 2025)
Research Originality: This study focused on addressing the goal of reducing extreme poverty (EP) to 0% by 2024 in Indonesia, an objective that has been underexplored in global literature. Research Objectives: This study examined convergence in EP across Indonesia and analyzed the impact of economic as well as social variables on poverty reduction. Research Methods: Panel data from 34 Indonesian provinces (2017–2022) were analyzed using Generalized Method of Moments (GMM) and K-means Cluster analysis for regional classification. Empirical Result: The results showed that provinces in Indonesia were reducing EP at an annual rate of 1.19%, with a half-life of 1.6 years. This process signified that the country was on a path to achieve near-zero EP by 2024. Major socioeconomic drivers identified during the study included employment expansion and investments in education. Moreover, K-means Cluster analysis identified Cluster 1 (Central Sulawesi, North Maluku, Papua) with the highest EP rate of 1.52%, showing critical geographic disparities. Implications: The Government should adopt a multilevel strategic framework prioritizing regions with the highest poverty rates. Job creation and better access to education played a crucial role. Additionally, Indonesia's success could serve as a model for sustainable EP eradication in developing nations. JEL Classification: I32, P46, Q01